Characteristics of referred patients with twin‐twin transfusion syndrome who did not undergo fetal therapy. (20th February 2019) - Sasso, Elizabeth B.; Hardley, Macy T.; Bottura, Isabela; Korst, Lisa M.; Ouzounian, Joseph G.; Chmait, Ramen H.
Abstract: Introduction: Abundant research has reported twin‐twin transfusion syndrome (TTTS) outcomes following fetal therapy. Our research describes TTTS patients who did not undergo fetal therapy. Methods: Records from TTTS pregnancies evaluated at 16 to 26 gestational weeks were reviewed between January 2006 and March 2017. The study population comprised subjects who did not undergo fetal therapy. Based on initial consultation, patients were grouped as nonsurgical vs surgical candidates. TTTS progression and perinatal outcomes were assessed. Results: Of 734 TTTS patients evaluated, 68 (9.3%) did not undergo intervention. Of these, 62% were nonsurgical candidates and 38% were surgical candidates. Nonsurgical candidates were ineligible for treatment because of fetal demise or maternal factors (placental abruption, severe membrane separation, and preterm labor). Of surgical candidates, 11 underwent expectant management, eight elected pregnancy termination, and seven planned fetal intervention but had a complication before the procedure. TTTS progression occurred in 10 (15.2%) of 66 cases. Neonatal survival in 64 cases was as follows: in 41 (64%), no survivors; in 11 (17.2%), one survivor; and in 12 (18.8%), two survivors. Conclusion: Nine percent of referred TTTS patients did not undergo fetal therapy, with many ineligible because of morbidity between referral and consultation. Studies of TTTS should acknowledge this subgroup and circumstances leading to lack of treatment. Abstract : What is already known about this topic? Current available information in the literature regarding the outcomes of patients with twin‐twin transfusion syndrome who are expectantly managed focuses on patients with stage I TTTS. Few studies report the natural history of TTTS diagnosed at all stages and none that describe the patient population and survival outcomes in nonsurgical candidates. What does this study add? The current study provides information to clinicians caring for patients with TTTS regarding modifying factors that impact eligibility to receive fetal therapy as well as survival outcomes of the subset of patients who are not candidates for surgical management.